Acute Lung Injury and Acute Respiratory Distress Syndrome Requiring Tracheal Intubation and Mechanical Ventilation in the Intensive Care Unit: Impact on Managing Uncertainty for Patient-Centered Communication. (September 2013) - Johnson, Robert F.; Gustin, Jillian
A case of acute lung injury (ALI) progressing to acute respiratory distress syndrome (ARDS) requiring tracheal intubation and mechanical ventilation (ETMV) is presented. The palliative medicine service was asked to address concerns expressed by the patient's spouse reflecting uncertainty regarding outcome expectations. Acknowledging and confronting the uncertainties of a critical illness is an essential component of patient-centered communication. Addressing and managing uncertainty for the case scenario requires consideration of both short- and long-term outcomes including mortality, ventilator independence, and adverse effects on quality of life for survivors. In this paper, ALI/ARDS requiring ETMV in the ICU was used as a focal point for preparing a prognostic assessment incorporating these issues. This assessment was based on a review of recently published literature regarding mortality and ventilator independence of survivors for adult patients receiving ETMV for ALI/ARDS in the ICU. In the studies reviewed, long-term survival reported at 60 days to 1 year was 50-73% with greater than 84% of the survivors in each study breathing independently. Selected articles discussing outcomes other than mortality or recovery of respiratory function, particularly quality of life implications for ALI/ARDS survivors, were also reviewed. A case of of ALI/ARDS requiring ETMV in the ICU is used to illustrate the situation of an incapacitated critically ill patient where the outcome is uncertain. Patient-centered communication should acknowledge and address this uncertainty. Managing uncertainty consists of effectively expressing a carefully formulated prognostic assessment and using sound communication principles to alleviate the distress associated with the uncertain outcome probabilities.